FATTY ACID COMPOSITION OF LIPIDS OF BACTERIA OF THE GENUS PSEUDOMONAS, OXIDIZING PETROLEUM PRODUCTS - Т. В. Гудзенко; Н. В. Коротаєва; О. В. Волювач; Т. О. Бєляєва; О. Г. Горшкова; В. О. Іваниця (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2014)
Aim. Determination of fatty acid composition of lipids and identification of strains of bacteria of the genus Pseudomonas, which oxidize crude oil and petroleum products. Methods. The fatty acid analysis of strains of Pseudomonas sp. ONU328 и Pseudomonas sp. ONU329 were carried out by gas chromatography using identification of microorganisms MIDI Sherlock (MIDI, USA). Results. The analysis of the results of gas chromatography showed that long-chain unsaturated and saturated fatty acids and branched structural isomers dominated in profile of fatty acid of the strains of Pseudomonas sp. ONU328 и Pseudomonas sp. ONU329. In the profiles of fatty acid of both strains there were detected hexadecanoic acid (C16:0) and hexadecanoic acid (C16:1 w7c/C16:1 w6c). This short-chain saturated hydroxy acids of the strain of Pseudomonas sp. ONU328 accounted for 12.6%, and the branched structural isomers of short-chain saturated hydroxy acids of the strain of Pseudomonas sp. ONU329 – up to 7% of the total peak areas. For the first time there were established that the closely related species of Pseudomonas were distinguished by the presence of cycloheptadecanoic acid of P. fluorescens ONU328 and 13-methyltetradecane acid (C15:0 iso), 12-methyltetradecane acid (C15:0 anteiso) of P. maltophilia ONU329. A distinctive indicator of their separation is a measure of unsaturations. Conclusion. The fatty acid composition of the investigated strains of Pseudomonas sp. ONU328 и Pseudomonas sp. ONU329 identified as Pseudomonas maltophilia ONU329 and Pseudomonas fluorescens ONU328. The peculiarities of fatty acid profile of the studied microorganisms were systematized and can be used as an auxiliary key for differentiation at the species level (according to a study in cellular fatty acid composition of bacteria in these species.